Association of decreased glomerular filtration rate with renal hemodynamic disorders and inflammatory biomarkers in patients with medically-controlled hypertension of high cardiovascular risk - O. A. Koshelskaya; O. A. Zhuravleva; I. V. Kologrivova; N. Yu. Margolis (Российский кардиологический журнал)
Aim. To assess markers of chronic kidney disease (CKD) in patients with medically-controlled hypertension (HTN) (<140/90 mm Hg), as well as to analyze potential association of decreased glomerular filtration rate (GFR) <60 ml/min/1,73 m2 with clinical data and therapy; to establish significant determinants of GFR decrease in this category of patients.Material and methods. The study included 70 patients with HTN and office blood pressure (BP) <140/90 mm Hg aged 64 (57; 68) years (men, 48,6%), of whom 40 patients were examined within the Russian multicenter CHRONOGRAPH program. Office BP was 130 (120; 140)/80 (72; 82) mm Hg. GFR and albuminuria were assessed. Twenty-four-hour BP monitoring and Doppler ultrasound of renal blood flow with estimation of resistance indices (RI) were performed. The content of highsensitivity C-reactive protein (hsCRP), interleukins (IL) 1β, 6, 10 and lipid transport function parameters was determined.Results. CKD markers were detected in 31,4% of patients (in 27,1% — a decrease in GFR <60 ml/min/1,73 m2; in 12,9% — pathological albuminuria). Patients with CKD markers were older, had higher office systolic BP and nocturnal pulse pressure, higher blood hsCRP and RI levels throughout the renal flow, and lower high-density lipoprotein cholesterol levels. In the presence of CKD markers, calcium channel blockers, aldosterone receptor antagonists and statins were used more often. The results of correlation analysis were used to determine the determinants of GFR decline. In the general group, GFR values had inverse correlations with age (Rs=-0,58, p<0,0001), segmental intrarenal artery RI (Rs= -0,4232, p=0,0005), blood hsCRP (Rs=-0,3998, p=0,0007), IL-1β (Rs=-0,3139, p=0,0086), office BP and some 24-hour BP parameters. In the presence of CKD markers, a direct association of GFR and IL-10 was determined (Rs=0,4293, p=0,046). In the absence of such markers, GFR had an inverse correlation with IL-1β content (Rs=-0,3110, p=0,0333). A multiple linear regression model included following independent determinants of GFR: age, blood hsCRP and RI in the segmental intrarenal arteries.Conclusion. Among patients with medically-controlled HTN of high cardiovascular risk, a high prevalence of CKD markers was revealed (31,4%). Compared with patients with preserved renal function, in the presence of CKD markers, there were higher levels of office systolic BP, nocturnal pulse pressure, blood hsCRP, and intrarenal artery RI. Associations were established between GFR and the levels of hsCRP, IL-1β and IL-10, which confirms the pathological role of inflammatory biomarkers in developing renal dysfunction in high-risk HTN. Age, elevated blood hsCRP levels, and intrarenal artery RI are independent determinants of decreased GFR in patients with medically-controlled HTN of high and very high cardiovascular risk. The data obtained shows the need for early prescription of combination antihypertensive therapy with nephro- and vasoprotective effects in this category of patients, as well as with an ability to depress the chronic subclinical inflammation.